Learning to learn English : a course in learner training : learner's book - Ellis, Gail.; Sinclair, Barbara (Cambridge : Cambridge University Press, 1989)
Through listening and speaking exercises, teaches basic techniques for learning English. Includes strategies for understanding people with accents, handling routine conversations, and speaking on the telephone.
Written by Gail Ellis and Barbara Sinclair.
Keywords: English language -- Textbooks for foreign speakers